Dynamic effects during a high-speed sinter-forging process - Jha A.K.; Kumar S. (My University, 2025)
The paper reports on an investigation into the various technological aspects of a high-speed sinter-forging process. Experiments were conducted and measurements were made in the development of barrelling, strain variations at the free surface and densification during dry and lubricated high-speed cold forging of sintered copper powder discs. The relationship between the frictional stress at the interface and other process variables is discussed and an analysis is given for the calculation of pressure distribution and die load by the solution of the equations of equilibrium taking barrelling into consideration for axial symmetry and plane strain sinter-forging conditions. Results are discussed critically to illustrate the interaction of various processing parameters involved during high-speed sinter-forging process and are presented graphically. Copyright © 1996 Elsevier Science Ltd.